The Quality of 'Whirling Tide' Clothes as a Creative Expression Media for Fashion Students - Titin Agustina; Sri Endah Wahyuningsih (Jurnal Penelitian Pendidikan, 2026)
This study aims to analyze the quality of the Whirling Tide fashion design as a form of creative expression by fashion education students based on six evaluation aspects, namely design, size, sewing technique, aesthetics, garment performance, and uniqueness. This research employed a quantitative approach with a descriptive method. Data were collected from 35 validators consisting of 5 expert validators and 30 trained validators using a Guttman-scale checklist instrument, and then analyzed using percentage analysis. The results show that the expert validators’ assessment reached 93.22%, while the trained validators’ assessment reached 97.11%, indicating that the Whirling Tide fashion design is categorized as very high quality. The aesthetics and uniqueness aspects obtained the highest scores, while the design aspect received the lowest score, although it still remained in the high-quality category. These findings indicate that Whirling Tide successfully integrates visual aesthetics, technical construction, cultural inspiration, and creative innovation as a fashion work. Therefore, this study can serve as a reference for evaluating fashion quality in fashion education, particularly in the development of creative works based on cultural and conceptual design.